What do we know about the role of lncRNAs in multiple sclerosis? - Viviana Nociti; Massimo Santoro (Neural Regeneration Research, 2021)
Multiple sclerosis is a chronic, inflammatory and degenerative disease of the central nervous system of unknown aetiology although well-defined evidence supports an autoimmune pathogenesis. So far, the exact mechanisms leading to autoimmune diseases are still only partially understood. We know that genetic, epigenetic, molecular, and cellular factors resulting in pathogenic inflammatory responses are certainly involved. Long non-coding RNAs (lncRNAs) are non-protein coding transcripts longer than 200 nucleotides that play an important role in both innate and acquired immunity, so there is great interest in lncRNAs involved in autoimmune diseases. The research on multiple sclerosis has been enriched with many studies on the molecular role of lncRNAs in the pathogenesis of the disease and their potential application as diagnostic and prognostic biomarkers. In particular, many multiple sclerosis fields of research are based on the identification of lncRNAs as possible biomarkers able to predict the onset of the disease, its activity degree, its progression phase and the response to disease-modifying drugs. Last but not least, studies on lncRNAs can provide a new molecular target for new therapies, missing, so far, a cure for multiple sclerosis. While our knowledge on the role of lncRNA in multiple sclerosis has recently improved, further studies are required to better understand the specific role of lncRNAs in this neurological disease. In this review, we present the most recent studies on molecular characterization of lncRNAs in multiple sclerosis disorder discussing their clinical relevance as biomarkers for diagnosis and treatments.